Spontaneous and perturbation-based EEG cortical excitability markers are associated with plasma p-tau181 concentration in healthy middle-aged adults - Ruben Perellón-Alfonso; Kilian Abellaneda-Pérez; Indre Pileckyte; María Cabello-Toscano; Lídia Mulet-Pons; Lídia Vaqué-Alcázar; Gabriele Cattaneo; María Redondo-Camós; Goretti España-Irla; Selma Delgado-Gallen; Javier Solana Sánchez; Henrik Zetterberg; et al. (Heliyon)
In early-stage Alzheimer's disease (AD) amyloid-β (Aβ) deposition can induce neuronal hyperactivity, thereby potentially triggering activity-dependent neuronal secretion of phosphorylated tau (p-tau), ensuing tau aggregation and spread. Therefore, cortical excitability is a candidate biomarker for early AD detection. Moreover, lowering neuronal excitability could potentially complement strategies to reduce Aβ and tau buildup. There is, however, a lack of understanding of the relationship between cortical excitability and p-tau increase in vivo. Therefore, in a sample of 658 healthy middle-aged (between the ages of 40 and 65) participants of the Barcelona Brain Health Initiative cohort study, we examined the relation of blood-based tau, phosphorylated at amino acid 181 (p-tau181), reflecting neuronal p-tau secretion; neurofilament light chain (NfL), as a passively released control for p-tau181; and electroencephalography (EEG) markers of cortical excitability. A subsample of 47 participants also completed a controlled brain perturbation approach via transcranial magnetic stimulation (TMS) with concurrent EEG. Results show that both spontaneous (i.e., resting-state) and perturbation-based TMS-EEG markers, are associated with blood p-tau181, particularly in older individuals. The perturbation-based marker was a significantly more sensitive predictor of p-tau181 concentration than the spontaneous resting state EEG-based marker. The relationships observed are not present for the NfL control. These results show that relationships between p-tau181 and cortical excitability are present in healthy middle-aged subjects and that p-tau181 increases may reflect activity-dependent secretion.